INSULIN-LOADED MICROEMULSION: FORMULATION, DEVELOPMENT, AND CHARACTERIZATION - SHUBHANGI RAHUL MORE; BHUSHANKUMAR S SATHE; SHASHI DAKSH (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objectives: The present investigation aimed to develop insulin loaded microemulsion using quillaja saponin as natural surfactant, isopropyl myristate along with linoleic acid as oil phase, isopropyl alcohol as co-surfactant. And dimethyl sulfoxide as permeation enhancer. Methods: Microemulsion was formulated employing conventional titration approach to identify composition that yield clear and stable microemulsion. Novel insulin-loaded microemulsion was assessed for multiple evaluation parameters like droplet size, zeta potential, in vitro skin permeation by Franz diffusion cell, permeation data analysis, and stability. Results: The pseudoternary phase diagram demonstrated that the oil phase entailing isopropyl myristate and linoleic acid performed exceptionally well at weight ratios (3:1) with quillaja saponin and co-surfactant. Average droplet size of freshly prepared microemulsion of optimized batch F6 was found to be 0.395 μm. Conclusion: Thus, it was concluded that small droplet size ensured optimal skin permeation and absorption by offering large surface area for interaction with biological membrane. Microemulsions exhibited stability. Thus, a simple manufacturing (conventional titration approach) proved promising for the treatment of diabetic management with developed novel insulin-loaded microemulsions.